Provisional Agenda for the Fourteenth Meeting of the International Monetary and Financial Committee (IMFC). (Policy Papers; Policy Paper ;, 2006)
Provisional agenda for the Fourteenth Meeting of the International Monetary and Financial Committee, which is to be convened on Sunday, September 17, 2006 in the Suntec Singapore International Convention and Exhibition Centre in Singapore.